Challenges for nurses in caring for patients with acute encephalitis: lack of knowledge, time and rehabilitation. (13th January 2022) - Gill, Claire; Griffiths, Mike; Easton, Ava; Solomon, Tom
Abstract : Aim: To explore the experiences of registered nurses providing care to adult patients affected by encephalitis, from admission into hospital through to discharge. Study design: A qualitative phenomenological methodology was used. Sample and setting: Eight registered nurses in a city centre teaching hospital. Methods: Data collection took place using in-depth, semi-structured interviews. Data were analysed and themes identified using framework analysis. Findings: Three key findings were identified: nurses felt that they lacked knowledge of encephalitis, lacked time to give these patients the care they needed, and they lacked access to rehabilitation for patients with encephalitis. Conclusion: This study provides the first evidence on nurses' experiences of providing care to patients affected by encephalitis. It has shown that they often lack the knowledge and time to give adequate support to patients. They also lack access to rehabilitation for these patients.